2018
DOI: 10.1002/maco.201709960
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rotation speed on mechanical properties and corrosion sensitivity of friction stir welded AA2024‐T3 joints

Abstract: A study of aluminum alloy 2024‐T3 friction stir welded (FSWed) joints under different rotation speeds at fixed travel speed of 200 mm/min is summarized. The effect of rotation speed on the hardness, tensile mechanical properties as well as corrosion sensitivity of the welded joints was explicitly investigated. The results show that the rotation speed has a remarkable influence on the shape and geometry of the stirred zone. Microstructure of the joint varied, while it was shown that microhardness was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Although good intermixing was obtained at 1400 rpm, the tensile strength began to decrease after 1100 rpm due to prolonged thermal exposure causing softening at HAZ. The tensile strength results of the present findings were also similar to those investigated by Li et al 36 and Liu et al 37 From the tensile test, it was clear that a joint made at a very high traverse speed without any defect failed at SZ (Figure 2(c)) due to lower intermixing between two dissimilar base materials. Therefore, to achieve higher tensile strength in FSWed dissimilar aluminium alloys, rotational speed also needs to be varied for proper intermixing in the SZ.…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…Although good intermixing was obtained at 1400 rpm, the tensile strength began to decrease after 1100 rpm due to prolonged thermal exposure causing softening at HAZ. The tensile strength results of the present findings were also similar to those investigated by Li et al 36 and Liu et al 37 From the tensile test, it was clear that a joint made at a very high traverse speed without any defect failed at SZ (Figure 2(c)) due to lower intermixing between two dissimilar base materials. Therefore, to achieve higher tensile strength in FSWed dissimilar aluminium alloys, rotational speed also needs to be varied for proper intermixing in the SZ.…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…1 A sizable number of studies have been reported highlighting the effect of the rotational and traverse speed on the evolution of FS weld microstructure and its resultant influence on properties. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] During the initial FSW study, Hashimoto et al 19 found that the tool travel and rotational speed affect the quality of joint and formation of the defect. The plunge depth was found to be important in void formation.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical equipment inevitably suffers from the severe environment and service conditions, usually accompanied by high/low temperature, salt spray, and acid/alkaline atmosphere. The resulting friction, wear, and corrosion are the most prominent factors that affect the service life and cause the material failure, 1,2 even badly damage during the whole life cycle. So it is of great significance to take effective protection for weakening or eliminating these conditions.…”
Section: Introductionmentioning
confidence: 99%